Digital media to inspire and sustain sport participation in urban areas - Rollinson, Benedict Douglas (Graduate School of Business (GSB), 2021)
This research looks to understand the role digital media plays to inspire and sustain sports participation and how digital media could be used as a socially inclusive tool. The study explores if strategically packaged digital media could be used in a socially inclusive way to increase or sustain sports participation. This would address one of the problems facing sports organisations, as sports participation is decreasing or at least stagnating both in South Africa and on a global scale. This study followed an exploratory, inductive approach, using Self-determination Theory (SDT) developed by Deci and Ryan (1985) as a theoretical framework. The paper looks to understand what research has been done to understand how people are motivated to participate in sport and the proven theories that have been tested (Pelletier et al., 1995) to understand the role of intrinsic motivation has as a powerful indicator of intention. This study made use of a qualitative, cross-sectional design and data was collected through semi-structured interviews with active participants based in Langa, Cape Town. The findings of this study showed the participants regularly accessed digital media in a manner which strongly aligned with the literature and has been shown to increase intrinsic motivation, which leads to action. The findings further show that sports media can be used as a tool for social inclusion, despite the participants socio-economic status they regularly accessed online sports content for motivational and learning purposes. Based on the findings of this research, sports organisations need to consider digital media as a viable and socially inclusive way to sustain or even increase sports participation.